Impact of the Use of a Teaching Toolbox in an Awareness Campaign on Children's Representations of Coral Reefs - Chabanet, Pascale; Stoica, Georgeta; Carrière, Stéphanie M.; Sabinot, Catherine; Bedrossian, Claire; Ferraris, Jocelyne (Frontiers in Marine Science, 2018)
Environmental education for children is one of the fundamental tools required to reverse the degradation of our environment and the biodiversity erosion. Currently coral reefs are part of the vulnerable ecosystems which are most threatened by human activities and climate change. Responding to these pressures demands decisions at multiple scales, based on solid knowledge of coral reefs but also on strengthened awareness to build adaptive management solutions. Here we evaluate the impact of an environmental awareness campaign for children using a teaching toolbox developed by scientists (MARECO “The Coral Reef In Our Hands”). To assess this impact before and after using the toolbox, we analyzed the evolution of children’s representations of coral reefs through drawings. This study was carried out in New Caledonia, focusing on five elementary schools in different social and cultural contexts (urban, rural and coastal). 248 drawings were made by children. The drawings were analyzed quantitatively using multivariate statistical analyses which reveals a diversity of representations in children with diverse sociocultural profiles, but also between schools, emphasizing that relationships with nature and marine environment vary according to direct and indirect experiences related to reefs. Furthermore, our results pointed out relevant differences in coral reef representations before and after the use of MARECO, particularly regarding their knowledge of reef biodiversity associated with multicolored organisms and the connection of coral reef with environment, the number of colors being used as a proxy of this global vision developed by children. These results point out the performance of MARECO as a playful tool to transfer scientific knowledge to children. Coral reef conservation is intimately linked to an awareness in young generations of the environmental challenges of tomorrow. To be agents of change in a sustainable world, children must be engaged in a fun, rigorous, action-oriented and socially responsible learning process such as the ones developed in participatory approaches.